CERIA-CARBONATE SOLID ELECTROLYTE COMPOZITE FOR INTERMEDIATE TEMPERATURE FUEL CELL - BALINT (SAMOILA), Adriana; RISTOIU, Tania; MESAROS, Amalia; NASUI, Mircea; MOS, Ramona; GABOR, Mihai; BOGDAN, Vasile; PETRISOR Jr., Traian; CIONTEA, Lelia (Studia Universitatis Babeș-Bolyai Ambientum, 2015)
Ceria based nanocomposites consisting of calcium doped ceria and Na2CO3 have been prepared for their use as solid state electrolyte in solid oxide fuel cells by a direct co-precipitation method followed by a thermal treatment at 700 0C. The decomposition course of the precursor, the thermal stability, the morphology, and the composite formation succession were studied by thermogravimetric analyses (TG), FT-IR spectroscopy, SEM and XRD analyses. The only identified crystalline phase is cerium oxide, in which the cerium ions are partially substituted by the calcium ions. The absence of any carbonate phase in the XRD pattern is indicative for its amorphous character. The calcium doped ceria crystallites, with an average size of about 50 nm, have a uniform distribution in the matrix. The temperature dependence of the conductivity between 300-600 0C was performed on the composite pellets, exhibiting an exponential behavior of the electrical conductivity with values intermediate between the calcium doped ceria and Na2CO3. The activation energy decreases from 1.693 eV for pure ceria to 0.79 eV for the calcium doped ceria nanocomposite.